2016
DOI: 10.1002/poc.3675
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, physicochemical, and biological activities of novel N-acyl tyrosine monomeric and Gemini surfactants in single and SDS/CTAB-mixed micellar system

Abstract: A series of single-chained N-acyl tyrosine surfactants with varying chain lengths (C 10 -C 18 ) and degree of unsaturation, as well as an N-acyl Gemini tyrosine surfactant with chain length C 12 , were synthesized, and the structures were confirmed using spectral analysis. The effect of chain length and level of unsaturation on the physicochemical and antibacterial properties of the N-acyl tyrosine surfactants was evaluated. The C 12 derivative displayed the optimum antibacterial activity among the single chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Evidence for the presence of N-acylated derivatives of aromatic or basic amino acids was mainly based on a multitude of environmental DNA libraries. Characterisation of biosynthetic pathways for N-acyl amino acids is an important task in the future given that such compounds find potential biotechnological applications as antimicrobial surfactants and precursors for biodegradable polyesters in pharmaceutical and biomedical applications 30,31 . In case of the surfactants, the C 12 chain as acyl residue (as present in stieleriacine A 1 ) proved to Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the presence of N-acylated derivatives of aromatic or basic amino acids was mainly based on a multitude of environmental DNA libraries. Characterisation of biosynthetic pathways for N-acyl amino acids is an important task in the future given that such compounds find potential biotechnological applications as antimicrobial surfactants and precursors for biodegradable polyesters in pharmaceutical and biomedical applications 30,31 . In case of the surfactants, the C 12 chain as acyl residue (as present in stieleriacine A 1 ) proved to Fig.…”
Section: Discussionmentioning
confidence: 99%
“…β = 0 stands to express the ideal mixing of the components (no net interaction). The more the value of β , the higher is the degree of interaction between the amphiphiles . The negative value of interaction parameter owes the hydrophobic interaction amid tails of the amphiphiles.…”
Section: Resultsmentioning
confidence: 99%
“…The more the value of β, the higher is the degree of interaction between the amphiphiles. [28,48] The negative value of interaction parameter owes the hydrophobic interaction amid tails of the amphiphiles. It was observed that the value of β rises with the enhancement of the mole fraction of CTAB in absence/occurrence of NH 2 -CO-NH 2 in almost all cases denotes the interaction between constituents enhances with an increase in mole fraction of CTAB (Tables 1-3).…”
Section: Interaction Parametermentioning
confidence: 99%
“…Thus, investigations of [Zn (II)-Trp] + and ninhydrin could be utilized as a simple and reliable kinetic probe in aggregated structural systems. The investigation may also be performed in the presence of gemini surfactant micelles [52][53][54][55][56] as well as mixed surfactant systems [57][58][59][60] for the enhanced utility of technique/method.…”
Section: Discussionmentioning
confidence: 99%